A high-reliability, long-lasting ant-proof cable and preparation method thereof
By adding surface-modified silica microcapsules to the cable PE outer sheath material, using their self-repair and ant-repellent functions, the problems of insufficient self-repair capabilities and power outages in the existing cable ant-proof technology are solved, and a high-reliability and long-term ant-proof effect is achieved.
Patent Information
- Application Number
- CN202411783225.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-06
AI Technical Summary
The existing cable ant prevention technology has the defects of insufficient self-repair capabilities and the need to rely on fault positioning technology and power outages, making it difficult to achieve long-term, high-reliable ant prevention effect.
The surface-modified silica microcapsules are added to the PE outer sheath material, silica as the capsule wall material, dicyclopentadiene and ant-proof agent as the capsule core material, and the polyethylene glycol monomethyl ether segment and n-nonolic vanillamide segment are modified on the surface of the silica to improve dispersion and ant-proof effect.
It achieves a high-reliability and long-term anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-anti-cell-capsule can effectively prevent termites and repair damage to the outer sheath of the cable without power outages and fault locations.
Smart Images

Figure CN119274856B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of cables, and in particular to a high-reliability, long-acting ant-proof cable and a preparation method thereof. Background Art
[0002] The research on cable anti-termite has started since the 1930s. Initially, the research direction of cable anti-termite was mainly drug-type anti-termite cable. For example, there was a study that mixed one of dieldrin, chlordane, heptachlor, lindane and other drugs with plastic. The results showed that the initial anti-termite effect was obvious, but after several years, the cable samples were taken back to measure the toxicity, and it was found that the toxicity had decreased. This was mainly due to the aging of the plastic and the gradual release of the drug. At the same time, the cable insulation sheath is in the outermost layer of the cable, which is the part of the cable that is most susceptible to external forces and external factors. Under the influence of external forces and external factors, the cable insulation sheath will produce cracks and other damages, thus providing a breakthrough for termites to bite. Therefore, it is necessary to regularly inspect and repair the cable. Conventional repair methods for repairing the cable insulation sheath include hot air welding, heat shrink tubing, and canned repair liquid, but these repair methods do not have self-repairing properties and need to rely on fault location technology to find the fault point before repairing. However, the cable lines are long and the laying methods are complicated. The existing fault location technology has limited accuracy, and it is difficult to accurately find the fault point. In addition, before repair, the covering soil needs to be dug, the wires need to be removed, and the power needs to be shut down, which requires a lot of manpower and material resources and affects normal production. Therefore, it is still necessary to develop a new high-reliability material with long-term anti-ant and self-repairing properties to solve the problem that the existing technology relies on fault location technology and requires power outages.
[0003] Self-repair, also known as self-healing, is the ability of a material to repair cracks and other defects without external force. Self-repair technology is divided into two types according to the self-repair mechanism: with repair agent (also called filling type) and without repair agent (also called intrinsic type). The self-repairing technology containing a repair agent encapsulates the repair agent through a carrier such as a hollow fiber, microcapsule, or microvessel and then implants it into the material. When the material is damaged by cracks or other damage, the cracks cause the carrier to rupture and release the repair agent. Under the action of the catalyst in the system, the monomers polymerize to fill the cracks and achieve self-repair. At present, commonly used microcapsule repair systems include epoxy resin-curing agent system, polar solvent-epoxy resin system, polydimethylsiloxane-butyltin catalyst system, and dicyclopentadiene (DCPD)-catalyst system. The dicyclopentadiene-catalyst system uses the ring-opening metathesis polymerization (ROMP) of dicyclopentadiene (DCPD) to generate polydicyclopentadiene (PDCPD) to repair the defective parts. The reaction rate is very fast, and the carbon-carbon double bonds are retained before and after the reaction, ensuring the toughness and strength of the repaired area. The system has a simple process, a wide range of applicable conditions and substrates, and good stability and comprehensive performance, and can be used as a candidate system for self-repairing insulating materials. However, the current wall material is mainly urea-formaldehyde resin, which is very brittle. When it accounts for more than 5wt% in the polyethylene material, the mechanical properties of polyethylene will drop significantly. But when the addition amount is too small, it is difficult to achieve a high degree of self-healing effect. Summary of the invention
[0004] In order to overcome the shortcomings of the above-mentioned prior art, the present invention provides a high-reliability and long-lasting ant-proof cable, wherein surface-modified silica microcapsules are added to the PE outer sheath material, silica is used as the capsule wall material of the self-repairing microcapsules, a repair agent and an anti-ant agent are used as the capsule core material, and a polyethylene glycol monomethyl ether segment with a dispersing effect and a nonanoic acid vanillamide segment with an anti-ant effect are modified on the surface of the silica, thereby achieving a high-reliability and long-lasting ant-proof effect.
[0005] The technical solution for achieving the purpose of the present invention is as follows:
[0006] A high-reliability and long-lasting ant-proof cable comprises, from inside to outside, a conductor, an insulating layer, a conductor shielding layer, an aluminum sheath and a PE outer sheath, wherein the PE outer sheath comprises the following components by weight: 100 parts of polyethylene, 20-50 parts of a thermoplastic elastomer, 10-30 parts of surface-modified silica microcapsules, 0.1-1 part of a catalyst, and 5-10 parts of an auxiliary agent, wherein the surface-modified silica microcapsules comprise, from inside to outside, a capsule core, a capsule wall and a modified layer, wherein the capsule core comprises dicyclopentadiene and an ant-proofing agent, the capsule wall is silica, and the modified layer comprises a polyethylene glycol monomethyl ether segment and a nonanoic acid vanillamide segment.
[0007] Specifically, the preparation method of the surface modified silica microcapsules is as follows:
[0008] S1. Preparation of silica microcapsules: Disperse dicyclopentadiene, anti-termite agent and emulsifier in deionized water, adjust the pH to 7-8, mechanically stir until a stable water-in-oil emulsion is formed, add tetraethyl orthosilicate and 3-(methacryloyloxy)propyltrimethoxysilane, stir evenly, then slowly drop hydrochloric acid into the emulsion to adjust the pH to 2.5, heat the emulsion, stir and react for a period of time to obtain silica microcapsules, wash and dry for later use;
[0009] S2. Preparation of polyethylene glycol monomethyl ether chain segment: In a nitrogen atmosphere, polyethylene glycol monomethyl ether and triethylene diamine were mixed, heated to 50°C~55°C, isocyanatepropyl triethoxysilane was added dropwise, the reaction temperature was controlled at 50-55°C, and the reaction was stirred for 3~6 hours to obtain a polyethylene glycol monomethyl ether chain segment with a silane group;
[0010] S3. Preparation of nonanoic acid vanillamide chain segment: Under nitrogen atmosphere, nonanoic acid vanillamide was dissolved in acetone, potassium carbonate was added as a catalyst, a chlorosilane coupling agent was added dropwise, and the reaction temperature was controlled at 50-60° C. for reflux reaction for 6-12 hours to obtain nonanoic acid vanillamide chain segment with silane group;
[0011] S4. The silica microcapsules prepared in step S1 are surface-modified with polyethylene glycol monomethyl ether segments and nonanoic acid vanillamide segments having silane groups to prepare surface-modified silica microcapsules.
[0012] Preferably, the total mass of the polyethylene glycol monomethyl ether chain segment and the nonanoic acid vanillamide chain segment is 1-10wt% of the silica microcapsule, and the mass ratio of the polyethylene glycol monomethyl ether chain segment to the nonanoic acid vanillamide chain segment is 1:(1-3).
[0013] Preferably, the anti-termite agent is selected from at least one of carbamate and pyrethroid.
[0014] Preferably, the anti-ant agent is a compound of carbamate and pyrethroid in a mass ratio of (1-3):1.
[0015] Preferably, the molecular weight of the polyethylene glycol monomethyl ether is 350-1000 g / mol, more preferably 400-550 g / mol.
[0016] Preferably, the chlorine-containing silane coupling agent includes at least one of 3-chloropropyltriethoxysilane, 3-chloropropyltrimethoxysilane, 3-chloropropylmethyldimethoxysilane and (3-chloropropyl)diethoxy(methyl)silane.
[0017] Preferably, the mass ratio of the dicyclopentadiene to the anti-termite agent is 1:1; the mass ratio of the tetraethyl orthosilicate to 3-(methacryloyloxy)propyltrimethoxysilane is (4-5):1, wherein 3-(methacryloyloxy)propyltrimethoxysilane is used to increase the compatibility of dicyclopentadiene and tetraethyl orthosilicate.
[0018] Preferably, the polyethylene is at least one of low-density polyethylene and linear low-density polyethylene.
[0019] Preferably, the thermoplastic elastomer comprises at least one of a polyolefin elastomer, a thermoplastic polyolefin or a thermoplastic vulcanizate.
[0020] Preferably, the catalyst is one or more of Grubbs first generation catalyst, Grubbs second generation catalyst, and Grubbs third generation catalyst.
[0021] Preferably, the auxiliary agent includes one or more of carbon black, antioxidant and lubricant.
[0022] Preferably, the antioxidant is a primary antioxidant and an auxiliary antioxidant in a mass ratio of (1-2):1; the primary antioxidant is a hindered phenol antioxidant, and the auxiliary antioxidant is a phosphite antioxidant.
[0023] Preferably, the lubricant is any one or more of low molecular weight esters, metal soaps, stearic acid complex esters, and amides.
[0024] Preferably, the PE outer sheath further comprises 10-30 parts by weight of a flame retardant.
[0025] Preferably, the flame retardant is selected from halogen-free flame retardants, and specifically can be selected from at least one of ammonium polyphosphate, piperazine pyrophosphate, melamine polyphosphate, melamine pyrophosphate, triazine carbonizing agent, and melamine cyanurate.
[0026] The present invention also protects a method for preparing the high-reliability and long-lasting ant-proof cable, comprising the following steps: polyethylene, thermoplastic elastomer, surface-modified silica microcapsules, catalysts, and additives are mixed and melt-extruded to obtain a PE outer sheath material, and then the PE outer sheath is extruded outside the cable aluminum sheath to obtain a high-reliability and long-lasting ant-proof cable.
[0027] Beneficial Effects
[0028] The present invention provides a high-reliability long-term anti-ant cable, which includes a conductor, an insulating layer, a conductor shielding layer, an aluminum jacket and a PE outer sheath from the inside to the outside. By adding surface-modified silica microcapsules as a long-term anti-ant repair agent to the PE outer sheath material, the following beneficial effects are achieved:
[0029] (1) As the capsule wall material of self-healing microcapsules, silica has high mechanical strength and good heat resistance. Increasing the proportion of surface-modified silica microcapsules in PE will not lead to a decrease in mechanical properties, and can even improve the mechanical strength of polyethylene.
[0030] (2) The surface of silica is modified with polyethylene glycol monomethyl ether segments and nonanoic acid vanillamide segments. The polyethylene glycol monomethyl ether segments improve the dispersibility of the surface-modified silica microcapsules, thereby ensuring the mechanical strength, ant repellent effect and self-healing effect of the cable outer sheath. Nonanoic acid vanillamide, also known as capsaicin, is a commonly used small molecule anti-ant agent. When used directly, it has poor dispersion effect and is easy to precipitate. Modifying it on the surface of silica not only improves the dispersion effect, but also makes the amide structure of the small molecule less likely to migrate and cause failure, thereby achieving a long-lasting anti-ant effect.
[0031] (3) The repair agent dicyclopentadiene and the anti-termite agent are added to the capsule core material. When the outer sheath of the cable is damaged due to external force, the repair agent and the anti-termite agent in the microcapsule are released at the same time. While preventing termites from gnawing on the gap, dicyclopentadiene can achieve self-repair under the action of the catalyst, achieving high reliability and long-term anti-termite performance through double barriers. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 is the synthetic reaction formula of the polyethylene glycol monomethyl ether chain segment of the present invention;
[0033] Figure 2 is the synthetic reaction formula of the nonanoic acid vanillamide chain segment of the present invention;
[0034] Figure 3 Schematic diagram of the synthesis of surface modified silica microcapsules of the present invention;
[0035] Figure 4 This is the infrared spectrum of the polyethylene glycol monomethyl ether segment and the nonanoic acid vanillamide segment. DETAILED DESCRIPTION
[0036] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0037] In the examples, the experimental methods used are conventional methods unless otherwise specified, and the materials, reagents, etc. used are all commercially available unless otherwise specified.
[0038] The raw materials used in the embodiments and comparative examples are described as follows:
[0039] PE;AGILITY™1021, The Dow Chemical Company;
[0040] Thermoplastic elastomer 1: thermoplastic vulcanized rubber, grade 281-87MED, ExxonMobil;
[0041] Thermoplastic elastomer 2: polyolefin elastomer, POE8137, Dow Chemical Company;
[0042] Tetraethyl orthosilicate: 95%, Guangdong Wengjiang Chemical Reagent Co., Ltd.;
[0043] 3-(Methacryloyloxy)propyltrimethoxysilane: 98%, Guangdong Wengjiang Chemical Reagent Co., Ltd.;
[0044] Dicyclopentadiene (DCPD): 97%, Guangdong Yunxing Biotechnology Co., Ltd.;
[0045] Catalyst: Grubbs second-generation catalyst, Jiangsu Sinoco Catalyst Co., Ltd.;
[0046] Emulsifier: sodium dodecylbenzene sulfonate (SDBS): 99%, Zhongshan Yuanda New Materials Co., Ltd.;
[0047] Anti-termite agent: a combination of carbamate and pyrethrin in a mass ratio of 1:1, wherein carbamate, 95%, is from Guangzhou Juntang Technology Co., Ltd.; pyrethrin, 95%, is from Shenzhen Lijing Biochemical Technology Co., Ltd.;
[0048] Hydrochloric acid: 2 mol / L hydrochloric acid aqueous solution;
[0049] Polyethylene glycol monomethyl ether 1: molecular weight 400, product code P2183, TCI (Shanghai) Chemical Industry Development Co., Ltd.
[0050] Polyethylene glycol monomethyl ether 2: molecular weight 550, product code P2184, TCI (Shanghai) Chemical Industry Development Co., Ltd.
[0051] Polyethylene glycol monomethyl ether 3: molecular weight 1000, product code P2185, TCI (Shanghai) Chemical Industry Development Co., Ltd.
[0052] Triethylenediamine: 99%, Zhongshan Dixin Chemical Co., Ltd.
[0053] Isocyanatepropyltriethoxysilane: 99%, Zhongshan Dixin Chemical Co., Ltd.
[0054] Chlorosilane coupling agent: 3-chloropropyltriethoxysilane, 98%, Guangdong Wengjiang Chemical Reagent Co., Ltd.;
[0055] n-N-nonanoic acid vanillamide, HD-99, Qingdao Haida Chemical;
[0056] Carbon black: PE2718, carbon black content 50wt%, carrier resin is polyethylene, the amount of carbon black in the table is the weight of pure carbon black after conversion;
[0057] Antioxidant: a mixture of antioxidant 1010 (SONOX) and antioxidant 168 (SONOX) in a mass ratio of 1:2, commercially available;
[0058] Lubricant: zinc stearate, commercially available;
[0059] Flame retardant: ammonium polyphosphate, commercially available;
[0060] Surface modified silica microcapsules 1: Homemade, the preparation method is as follows:
[0061] S1. 10 parts by weight of molten dicyclopentadiene, 10 parts by weight of an anti-termite agent, 0.5 parts by weight of an emulsifier and 100 parts by weight of deionized water are mixed, stirred at 40°C at a speed of 400 rpm, the pH value of the system is adjusted to 7-8 by hydrochloric acid, and stirring is continued until a stable oil-in-water emulsion is formed; 20 parts by weight of tetraethyl orthosilicate and 5 parts by weight of 3-(methacryloyloxy)propyltrimethoxysilane are added to the emulsion, stirred evenly, hydrochloric acid is slowly added dropwise to the emulsion to adjust the pH value to 2.5, the emulsion is heated to 50°C and reacted at a speed of 300 r / min for 24 hours to obtain silica microcapsules, and the product is washed with acetone and deionized water in turn, dried naturally, and set aside;
[0062] S2. Preparation of polyethylene glycol monomethyl ether chain segment: Under a nitrogen atmosphere, 1 mol of polyethylene glycol monomethyl ether 1 and 1 mol of triethylene diamine were mixed, heated to 50° C., 1.2 mol of isocyanatepropyltriethoxysilane was added dropwise, the reaction temperature was controlled at 50-55° C., and the reaction was stirred for 6 hours. After the reaction, water was added to the system, and then extracted with ethyl acetate 3 times. The organic phases were combined and washed with brine, dried over anhydrous sodium sulfate, and purified by silica gel column chromatography to obtain polyethylene glycol monomethyl ether chain segments with silane groups; the yield was 91%. The infrared spectrum of the product was measured using a Nicoleti S50 Fourier transform infrared absorption spectrometer, as shown in FIG. Figure 4 As shown, from the red light spectrum, it can be seen that the polyethylene glycol monomethyl ether chain segment with silane groups simultaneously exhibits the characteristic peaks of Si-O and NH, proving that the polyethylene glycol monomethyl ether chain segment with silane groups is successfully synthesized;
[0063] S3. Preparation of nonanoic acid vanillamide chain segment: Under nitrogen atmosphere, 1 mol of nonanoic acid vanillamide was dissolved in acetone, 2 mol of potassium carbonate and 1.2 mol of chlorosilane coupling agent were added, the reaction temperature was controlled at 60°C for reflux reaction for 12 hours, water was added to the system after the reaction, and then extracted with ethyl acetate three times, the organic phases were combined and washed with brine, dried over anhydrous sodium sulfate, and purified by silica gel column chromatography to obtain nonanoic acid vanillamide chain segment with silane group; the infrared spectrum of the product was measured using Nicoleti S50 Fourier transform infrared absorption spectrometer, as shown in FIG. Figure 4 As shown, it can be seen from the red light spectrum that the n-nonanoic acid vanillamide segment with a silane group simultaneously exhibits the characteristic peaks of Si-O and NH, proving that the n-nonanoic acid vanillamide segment with a silane group was successfully synthesized;
[0064] S4. Disperse 10 parts by weight of the silica microcapsules obtained in step S1 in 200 parts by weight of anhydrous ethanol and stir to disperse them evenly at room temperature, mix the polyethylene glycol monomethyl ether segment with a silane group and the nonanoic acid vanillamide segment with a silane group with water in a weight ratio of 1:2 and stir to fully hydrolyze them, wherein the total weight of the polyethylene glycol monomethyl ether segment with a silane group and the nonanoic acid vanillamide segment with a silane group is 0.5, and the mass ratio of the polyethylene glycol monomethyl ether segment with a silane group to the nonanoic acid vanillamide segment with a silane group is 1:1, pour the aqueous solution system into the anhydrous ethanol system, stir at 70°C, condense and mix for 3 hours, and after the reaction is completed, wash with anhydrous ethanol for 3 times, filter until the filtrate is clear, and obtain surface-modified silica microcapsules, which are then dried at 70°C.
[0065] Surface modified silica microcapsule 2: The preparation method is different from that of surface modified silica microcapsule 1, except that in step S2, polyethylene glycol monomethyl ether 1 is replaced by polyethylene glycol monomethyl ether 2;
[0066] Surface modified silica microcapsule 3: The preparation method is different from that of surface modified silica microcapsule 1, except that in step S2, polyethylene glycol monomethyl ether 1 is replaced by polyethylene glycol monomethyl ether 3;
[0067] Surface modified silica microcapsule 4: Preparation method Compared with the surface modified silica microcapsule 1, the difference is that the total weight of the polyethylene glycol monomethyl ether segment with silane group and the nonanoic acid vanillamide segment with silane group is 1;
[0068] Surface modified silica microcapsule 5: Preparation method Compared with the surface modified silica microcapsule 1, the difference is that the total weight of the polyethylene glycol monomethyl ether segment with silane group and the nonanoic acid vanillamide segment with silane group is 0.1;
[0069] Surface modified silica microcapsule 6: Preparation method Compared with the surface modified silica microcapsule 1, the difference is that the mass ratio of the polyethylene glycol monomethyl ether segment with silane group and the nonanoic acid vanillamide segment with silane group is 0:1;
[0070] Surface modified silica microcapsule 7: Preparation method Compared with the surface modified silica microcapsule 1, the difference is that the mass ratio of the polyethylene glycol monomethyl ether segment with silane group and the nonanoic acid vanillamide segment with silane group is 1:0;
[0071] Silica microcapsules: homemade, the preparation method is as follows: 10 parts by weight of molten dicyclopentadiene, 10 parts by weight of anti-termite agent, 0.5 parts by weight of emulsifier and 100 parts by weight of deionized water are mixed, stirred at 400 rpm at 40°C, the pH value of the system is adjusted to 7-8 with dilute hydrochloric acid, and stirring is continued until a stable oil-in-water emulsion is formed; 20 parts by weight of tetraethyl orthosilicate is added to the emulsion, stirring is continued to form a stable oil-in-water emulsion, hydrochloric acid is slowly added dropwise to the emulsion to adjust the pH value to 2.5, the emulsion is heated to 50°C and reacted at a speed of 300 r / min for 24 hours to obtain silica microcapsules, the product is washed with acetone and deionized water in turn, dried naturally, and set aside;
[0072] Unless otherwise specified, the components and raw materials used in the embodiments and comparative examples of the present invention are all commercially available raw materials, and the components and raw materials used in each parallel experiment are all of the same kind.
[0073] Embodiments 1 to 7
[0074] A highly reliable and long-lasting anti-ant cable includes, from the inside to the outside, a conductor, an insulating layer, a conductor shielding layer, an aluminum sheath and a PE outer sheath. The PE outer sheath is formed by mixing polyethylene, a thermoplastic elastomer, a surface-modified silica microcapsule, a catalyst and an additive and then melt-extruded. The specific formula is shown in Table 1. A layer of PE outer sheath with a thickness of about 5 mm is extruded outside the cable aluminum sheath.
[0075] Comparative Examples 1 to 3
[0076] Compared with Examples 1 to 7, the difference is that the formula of the PE outer sheath is different, and the specific formula is shown in Table 1.
[0077] Table 1 PE outer sheath formula (weight parts)
[0078]
[0079] The PE outer sheath of a high-reliability and long-lasting ant-proof cable prepared in Examples 1-7 and Comparative Examples 1-3 was subjected to the following performance tests, and the results are shown in Table 2.
[0080] 1. Tensile strength: The tensile strength of the PE outer sheath of the anti-ant cable of the embodiment and the comparative example was tested according to the standard GB / T 11017.1-2014;
[0081] 2. Elongation at break: The elongation at break of the PE outer sheath of the anti-ant cable of the embodiment and the comparative example was tested according to the standard GB / T 11017.1-2014;
[0082] 3. Initial anti-ant performance: The anti-ant cables of the embodiment and the comparative example were tested according to the ant nest method of standard GB / T2951.38-1986, and the corrosion levels were recorded;
[0083] 4. Anti-ant performance after aging: The anti-ant cable was placed in a heat aging test chamber at 70°C for aging treatment. After 500 hours, the products of the embodiment and the comparative example were tested according to the ant nest method of standard GB / T2951.38-1986, and the corrosion level was recorded;
[0084] 5. Anti-ant performance after damage by external force: Place the anti-ant cable, blade and wood chip in order from bottom to top, load a weight of 30 kg on the wood chip, and push the wood chip from front to back to form scratches on the surface of the PE outer sheath of the anti-ant cable. Use a stereo microscope to photograph and measure the depth of the scratch, which is recorded as d1. Place the anti-ant cable with scratches in an ant nest, and test the products of the embodiment and the comparative example according to the ant nest method of standard GB / T2951.38-1986. Record the decay grade and the degree of repair after biting. The depth of the scratch after repair is recorded as d2. Repair efficiency = (d1-d2) / d1×100%.
[0085] Table 2 Performance test results of PE outer sheath
[0086]
[0087] The present invention adds surface modified silica microcapsules to the PE outer sheath material, wherein silica is used as the capsule wall material of the self-repairing microcapsules, which has an enhancing effect on the PE outer sheath material; polyethylene glycol monomethyl ether segments with a dispersing effect and nonanoic acid vanillamide segments with an anti-ant effect are modified on the surface of silica, thereby ensuring uniform dispersion of silica microcapsules in PE. When the surface of the PE outer sheath is intact, the nonanoic acid vanillamide segments on the surface of the silica microcapsules exert an ant-repelling effect. When the PE outer sheath is damaged due to aging, resulting in a decrease in the efficacy of the ant-repelling drug or external force, causing termites to bite, the silica microcapsules inside are bitten, and the anti-ant agent and repair agent of the capsule core are released, so that the termites are expelled in time and the damaged sites are repaired, thereby achieving a high reliability and long-term anti-ant effect through a double anti-ant barrier.
[0088] It can be seen from the data of Example 2 and Comparative Examples 1 to 3 that when the surface of the silica microcapsule is not modified with polyethylene glycol monomethyl ether chain segments, due to its poor dispersion effect, when the damaged site on the surface of the PE outer sheath is just not distributed with silica microcapsules, the self-repairing performance cannot be triggered in time, and the mechanical strength of the PE outer sheath, the anti-termite performance after aging, and the self-repairing effect are not good; when the surface of the silica microcapsule is not modified with nonanoic acid vanillamide chain segments, since the anti-termite agent is coated in silica, it can only be released after the cable is bitten by termites, and then self-repair behavior is performed, but at this time the cable is already deeply damaged, and the repair can only reach 75% of the effect. Comparative Example 3 does not perform surface modification on the silica microcapsules, and does not add 3-(methacryloyloxy)propyltrimethoxysilane as a compatibilizer in the interfacial polymerization, and the dispersion effect and repair effect are relatively poor.
[0089] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A high-reliability and long-lasting anti-ant cable, characterized in that: The invention comprises, from the inside to the outside, a conductor, an insulating layer, a conductor shielding layer, an aluminum jacket and a PE outer sheath. The PE outer sheath comprises, by weight, the following components: 100 parts of polyethylene, 20-50 parts of thermoplastic elastomer, 10-30 parts of surface-modified silica microcapsules, 0.1-1 parts of catalysts, and 5-10 parts of additives. The surface-modified silica microcapsules comprise, from the inside to the outside, a capsule core, a capsule wall and a modified layer. The material of the capsule core is dicyclopentadiene and an anti-termite agent, the material of the capsule wall is silica, and the material of the modified layer is a polyethylene glycol monomethyl ether segment and a nonanoic acid vanillamide segment. The preparation method of the surface-modified silica microcapsules is as follows: S1. Preparation of silica microcapsules: Disperse dicyclopentadiene, anti-termite agent and emulsifier in deionized water, adjust the pH to 7-8, mechanically stir until a stable water-in-oil emulsion is formed, add tetraethyl orthosilicate and 3-(methacryloyloxy)propyltrimethoxysilane, stir evenly, then slowly drop hydrochloric acid into the emulsion to adjust the pH to 2.5, heat the emulsion, stir and react for a period of time to obtain silica microcapsules, wash and dry for later use; S2. Preparation of polyethylene glycol monomethyl ether chain segment: In a nitrogen atmosphere, polyethylene glycol monomethyl ether and triethylene diamine were mixed, heated to 50°C~55°C, isocyanatepropyl triethoxysilane was added dropwise, the reaction temperature was controlled at 50-55°C, and the reaction was stirred for 3~6 hours to obtain a polyethylene glycol monomethyl ether chain segment with a silane group; S3. Preparation of nonanoic acid vanillamide chain segment: Under nitrogen atmosphere, nonanoic acid vanillamide was dissolved in acetone, potassium carbonate was added as a catalyst, a chlorosilane coupling agent was added dropwise, and the reaction temperature was controlled at 50-60° C. for reflux reaction for 6-12 hours to obtain nonanoic acid vanillamide chain segment with silane group; S4. The silica microcapsules prepared in step S1 are surface-modified with polyethylene glycol monomethyl ether segments and nonanoic acid vanillamide segments having silane groups to prepare surface-modified silica microcapsules.
2. The high-reliability and long-lasting anti-ant cable according to claim 1, characterized in that: The total mass of the polyethylene glycol monomethyl ether chain segment and the nonanoic acid vanillamide chain segment is 1-10wt% of the silica microcapsule, and the mass ratio of the polyethylene glycol monomethyl ether chain segment to the nonanoic acid vanillamide chain segment is 1:(1-3).
3. The high-reliability and long-lasting anti-ant cable according to claim 1 is characterized in that: The anti-termite agent is selected from at least one of carbamate and pyrethrin.
4. The high-reliability and long-lasting anti-ant cable according to claim 3, characterized in that: The anti-ant agent is a compound of carbamate and pyrethrin in a mass ratio of (1-3):
1.
5. The high-reliability and long-lasting anti-ant cable according to claim 1, characterized in that: The molecular weight of the polyethylene glycol monomethyl ether is 350-1000 g / mol.
6. The high-reliability and long-lasting anti-ant cable according to claim 1, characterized in that: The polyethylene is at least one of low-density polyethylene and linear low-density polyethylene; the thermoplastic elastomer includes at least one of polyolefin elastomer and thermoplastic vulcanized rubber; the catalyst is one or more of Grubbs first-generation catalyst, Grubbs second-generation catalyst and Grubbs third-generation catalyst.
7. The high-reliability and long-lasting anti-ant cable according to claim 1, characterized in that: The auxiliary agent includes one or more of carbon black, antioxidant and lubricant.
8. The high-reliability and long-lasting anti-ant cable according to claim 7, characterized in that: The antioxidants are a primary antioxidant and an auxiliary antioxidant in a mass ratio of (1-2):1; the primary antioxidant is a hindered phenol antioxidant, and the auxiliary antioxidant is a phosphite antioxidant; the lubricant is any one or more of low molecular weight esters, metal soaps, stearic acid complex esters, and amides.
9. The method for preparing the high-reliability and long-lasting anti-ant cable according to any one of claims 1 to 8, characterized in that: The method comprises the following steps: polyethylene, thermoplastic elastomer, surface modified silica microcapsules, catalysts and additives are mixed and melt-extruded to obtain a PE outer sheath material, and then the PE outer sheath is extruded outside the cable aluminum sheath to obtain a highly reliable and long-lasting ant-proof cable.
Citation Information
Patent Citations
Preparation method of termite-proof cable
CN114551002A
Waterproof photovoltaic cable and processing technology thereof
CN117012469A
Polyvinyl self-repairing composite medium with three-layer shell-core microcapsule gradient arrangement structure and preparation method of polyvinyl self-repairing composite medium
CN117327336A